Socially Demoralizing Environments and the Development of the Street Code from Childhood to Emerging Adulthood - Berg, Mark T. (Journal of quantitative criminology, 2020)
This study examines hypotheses regarding patterns of developmental change in street code commitment from childhood through emerging adulthood. It tests whether street code commitment demonstrates developmental stability or if it fluctuates in response to evolving socially demoralizing conditions.